Sintered neodymium-iron-boron permanent magnet and preparation method and application thereof

By controlling the nitrogen content in raw materials and airflow grinding, a reasonable distribution of nitrogen-rich and nitrogen-poor phases is formed, the problem of controlling nitrogen content in neodymium-ferrous boron magnets is solved, and the magnetic and mechanical properties of the magnet are improved.

CN119763965AActive Publication Date: 2025-04-04YANTAI ZHENGHAI MAGNETIC MATERIAL CO LTD

Patent Information

Application Number
CN202411972485.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-04
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

The prior art is difficult to effectively control the nitrogen content in neodymium iron boron magnets, resulting in the impact of magnetic properties and corrosion resistance, and common methods have problems of high cost and poor performance.

Method used

By controlling the nitrogen content of each element in the raw material, alloy scales with different nitrogen content are prepared, and the nitrogen content distribution is regulated during the airflow grinding process to form a reasonable distribution of nitrogen-rich and nitrogen-poor phases, and the magnetic and mechanical properties of the magnet are optimized.

Benefits of technology

Effective control of nitrogen elements in neodymium iron boron magnets is achieved, the magnetic and mechanical properties of the magnets are improved, and the problems of poor performance and high cost in the prior art are solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119763965A_ABST
    Figure CN119763965A_ABST
Patent Text Reader

Abstract

The invention discloses a sintered neodymium-iron-boron permanent magnet and a preparation method and application thereof.According to the formula of the permanent magnet, the specific ratio of R to Cu to B is adopted, the nitrogen content of a product in different stages is controlled, especially targeted intervention is conducted in the forming stages of a nitrogen-rich phase and a nitrogen-poor phase, reasonable distribution of the nitrogen-rich phase and the nitrogen-poor phase is guaranteed, and the performance of the sintered neodymium-iron-boron permanent magnet is improved. And the mechanical property and the magnetic property are synchronously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of rare earth permanent magnet materials and preparation thereof, and in particular relates to a sintered NdFeB permanent magnet and a preparation method and application thereof. Background Art

[0002] In the production process of NdFeB magnets, impurity elements are often inevitably introduced, and as the particle size of the magnetic powder decreases, the content of impurity elements, especially nitrogen, tends to increase significantly.

[0003] The most common method for controlling the nitrogen content is to use a more inert gas (such as helium, argon, etc.) as a protective gas in the production process, but this method has the disadvantages of high density and high cost of helium and argon, making it difficult to produce on a large scale. Other control methods include adding a certain amount of organic matter, but this method will lead to a sharp increase in another impurity element, carbon, which will have an adverse effect on product performance.

[0004] Regarding the distribution and influence of nitrogen, the prior art is limited to the influence of nitrogen content in macroscopic magnets on performance. It is generally believed that a relatively low nitrogen content will be more beneficial to the performance of NdFeB magnets. For example, patent document CN118299137A discloses that by controlling the relationship between the average grain size and nitrogen content of RTB permanent magnets, the uniform distribution of nitrogen in the magnet is ensured, and the formation of RN-rich areas is avoided or minimized, the magnetic properties and corrosion resistance of the magnet can be improved. However, this method does not control the nitrogen content, and it is difficult to obtain higher performance products. Summary of the invention

[0005] In order to improve the above technical problems, the present invention provides a sintered NdFeB permanent magnet, wherein the permanent magnet has main phase grains and grain boundary phases, wherein the grain boundary phases are located between the main phase grains; the components of the main phase grains include R2T 14 B; the grain boundary phase comprises a nitrogen-rich phase and a nitrogen-poor phase; wherein,

[0006] The nitrogen-rich phase comprises R, T, N, M and B, wherein, by mass ratio, R accounts for 45-75wt%, T accounts for 1-20wt%, N accounts for 10-35wt%, M accounts for 5-10wt%, and B accounts for 1-4wt%;

[0007] The nitrogen-poor phase comprises R, T, N and M, wherein, by mass ratio, R accounts for 45-75wt%, T accounts for 5-40wt%, N accounts for 0.01-5wt%, and M accounts for 10-35wt%;

[0008] R is a rare earth element; M is at least one of Al, Cu, Ga, Zr, Ti, Nb or Mn; N is nitrogen; T is at least one of Fe and Co; and B is boron.

[0009] According to an embodiment of the present invention, R is a rare earth element, which includes at least Nd. Further, R may also include at least one selected from the following rare earth elements: Y, La, Ce, Pr, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Sc.

[0010] According to an embodiment of the present invention, the nitrogen-rich phase is composed of R, T, N, M and B, wherein, by mass ratio, R accounts for 45-75wt%, T accounts for 1-20wt%, N accounts for 10-35wt%, M accounts for 5-10wt%, and B accounts for 1-4wt%.

[0011] According to an embodiment of the present invention, the nitrogen-poor phase is composed of R, T, N and M, wherein, by mass ratio, R accounts for 45-75wt%, T accounts for 5-40wt%, N accounts for 0.01-5wt%, and M accounts for 10-35wt%.

[0012] According to an embodiment of the present invention, in the nitrogen-rich phase, R accounts for 60-72wt% by mass, for example, 60wt%, 62wt%, 64wt%, 66wt%, 68wt%, 70wt%, 71wt% or 72wt%.

[0013] According to an embodiment of the present invention, in the nitrogen-rich phase, T accounts for 5-10wt% by mass, for example, 5wt%, 6wt%, 7wt%, 8wt%, 9wt% or 10wt%.

[0014] According to an embodiment of the present invention, in the nitrogen-rich phase, N accounts for 12 to 20 wt% by mass, for example, 12 wt%, 14 wt%, 15 wt%, 16 wt%, 17 wt%, 18 wt% or 20 wt%.

[0015] According to an embodiment of the present invention, in the nitrogen-rich phase, M accounts for 5 to 8 wt% by mass, for example, 5 wt%, 6 wt%, 7 wt% or 8 wt%.

[0016] According to an embodiment of the present invention, in the nitrogen-rich phase, B accounts for 1 to 3 wt% by mass, for example, 1 wt%, 2 wt% or 3 wt%.

[0017] According to an embodiment of the present invention, in the nitrogen-lean phase, R accounts for 48 to 56 wt% by mass, for example, 48 wt%, 49 wt%, 50 wt%, 51 wt%, 52 wt%, 53 wt%, 54 wt%, 50 wt%, 55 wt% or 56 wt%.

[0018] According to an embodiment of the present invention, in the nitrogen-poor phase, T accounts for 28 to 32.5 wt% by mass, for example, 28.0 wt%, 29.0 wt%, 29.5 wt%, 30.0 wt%, 30.5 wt%, 31.0 wt%, 31.5 wt%, 32.0 wt% or 32.5 wt%.

[0019] According to an embodiment of the present invention, in the nitrogen-depleted phase, the proportion of N by mass ratio is 0.1-2wt%, for example, 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1.0wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt%, 1.5wt% or 2.0wt%.

[0020] According to an embodiment of the present invention, in the nitrogen-depleted phase, M accounts for 10 to 18 wt% by mass, for example, 10 wt%, 11 wt%, 12 wt%, 13 wt%, 14 wt%, 15 wt%, 16 wt%, 17 wt% or 18 wt%.

[0021] According to an embodiment of the present invention, the ratio of the nitrogen-rich phase to the area of ​​the grain boundary phase is X1, and the ratio of the nitrogen-poor phase to the area of ​​the grain boundary phase is X2, 10%<X1≤25%, 69%≤X2≤85%. Preferably, 13%≤X1≤21%, for example, X1 is 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20% or 21%. Preferably, 70%≤X2≤84%, more preferably, 78%≤X2≤83%, for example, X2 is 78%, 79%, 80%, 81%, 82% or 83%.

[0022] According to an embodiment of the present invention, the sintered NdFeB permanent magnet, calculated by mass ratio as 100%, comprises the following components:

[0023] R: 26-32 wt%, R is a rare earth element, which includes at least Nd and at least one selected from the following rare earth elements: Y, La, Ce, Pr, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Sc;

[0024] M: 0.5-3wt%, M is at least one of Al, Cu, Ga, Zr, Ti, Nb, and Mn;

[0025] N: 0.02-0.1 wt%, N is nitrogen;

[0026] B: 0.9-1.1 wt%, B is boron;

[0027] The balance is T and impurities, T is at least one of Fe and Co, and the impurities are unavoidable impurities.

[0028] According to an embodiment of the present invention, M includes at least Cu, and may also be selected from at least one of Al, Ga, Zr, Ti, Nb, and Mn;

[0029] In the permanent magnet, the Cu content is 0.35-1.2 wt%, preferably 0.35-1.1 wt%.

[0030] According to an embodiment of the present invention, [R]-25*[Cu]-[B]≥0, preferably [R]-25*[Cu]-[B]≥2, and further preferably, 23≥[R]-25*[Cu]-[B]≥2; wherein [R], [Cu] and [B] are the mass percentages of R, Cu and B respectively.

[0031] The present invention has found that R, Cu, and B satisfy the relationship [R]-25*[Cu]-[B]≥0, and the synergistic effect of the nitrogen content of the raw materials and the nitrogen content of the air flow mill makes the proportion of the nitrogen-poor phase to the area of ​​the grain boundary phase 69%≤X2≤85%, which can achieve lattice structure regulation, affect the interaction between atoms and the distribution of electronic states, and further change the magnetic performance parameters such as the magnetic anisotropy of the grain boundary phase, thereby optimizing the magnetic properties of the magnet.

[0032] According to an embodiment of the present invention, in the permanent magnet, based on the mass of the permanent magnet, the mass percentage content of R is greater than 28.50wt% and less than 32.50wt%, for example, 29.0wt%, 29.5wt%, 30.0wt%, 30.5wt%, 31.0wt%, 31.5wt%, 32.0wt%, 32.5wt%.

[0033] According to an embodiment of the present invention, in the permanent magnet, based on the mass of the permanent magnet, the total mass percentage content of M is greater than 0.50wt% and less than 3.0wt%; for example, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1.0wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt%, 1.5wt%, 2.0wt%, 2.5wt% or 3.0wt%.

[0034] According to an embodiment of the present invention, in the permanent magnet, based on the mass of the permanent magnet, the content of N is 0.02 wt%, 0.04 wt%, 0.06 wt%, 0.08 wt% or 0.1 wt%.

[0035] According to an embodiment of the present invention, in the permanent magnet, based on the mass of the permanent magnet, the mass percentage content of B is greater than 0.90 wt % and less than 1 wt %, for example, 0.90 wt %, 0.95 wt %, or 1 wt %.

[0036] The present invention also provides a method for preparing the sintered NdFeB permanent magnet, the method comprising:

[0037] The raw materials for preparing the sintered NdFeB permanent magnet are sequentially subjected to a smelting process, a powder making process, a pressing process and a heat treatment process to prepare the sintered NdFeB permanent magnet.

[0038] According to an embodiment of the present invention, the raw materials for preparing the sintered NdFeB permanent magnet include:

[0039] R: 26-32 wt%, R is a rare earth element, which includes at least Nd and at least one selected from the following rare earth elements: Y, La, Ce, Pr, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Sc;

[0040] M: 0.5-3wt%, M is at least one of Al, Cu, Ga, Zr, Ti, Nb, and Mn;

[0041] B: 0.9-1.1wt%;

[0042] The balance is T and impurities; T is at least one of Fe and Co.

[0043] According to an embodiment of the present invention, in the smelting process, the nitrogen content of the rare earth raw material R (for example: PrNd) used is a, the nitrogen content of T (for example: Fe) is b, and the nitrogen content of BT (for example: BFe) is c, and a, b, and c satisfy: a<50ppm, b<100ppm, c<50ppm.

[0044] Preferably, a is 10 to 45 ppm, more preferably 10 to 30 ppm, and for example 10 to 25 ppm.

[0045] Preferably, b is 10 to 90 ppm, more preferably 10 to 60 ppm, and for example 10 to 40 ppm.

[0046] Preferably, c is 5 to 45 ppm, more preferably 9 to 30 ppm, and for example 9 to 25 ppm.

[0047] According to an embodiment of the present invention, alloy flakes are obtained after the smelting process. The smelting process can be performed by methods known in the art, such as the method of rapid solidification and strip throwing to make alloy flakes. Exemplarily, the smelting process for preparing alloy flakes is as follows: each raw material is heated to 1300-1600°C by electromagnetic induction to melt, and then the molten alloy is poured on a quenching roller (preferably a polished quenching roller), and alloy flakes are obtained after cooling.

[0048] According to an embodiment of the present invention, the powder making process includes hydrogen embrittlement, intermediate grinding and / or air flow grinding, and air flow milled powder is obtained after the powder making process is completed.

[0049] Specifically, during the jet milling process, the temperature of each material is ≤15°C.

[0050] Preferably, the hydrogen embrittlement, intermediate grinding and / or air flow grinding can be carried out by methods known in the art, as long as the air flow milled powder can be obtained.

[0051] According to an embodiment of the present invention, during the jet milling process, the grinding temperature is between -5 and 10°C or the initial temperature of the ground powder is between 0 and 15°C. For example, the grinding temperature is -5°C, -2°C, 0, 2°C, 4°C, 6°C, 8°C or 10°C; for example, the initial temperature of the ground powder is 0, 2°C, 4°C, 6°C, 8°C, 10°C, 12°C, 14°C or 15°C.

[0052] Under conventional processes, nitrogen elements tend to react rapidly with more active grain boundary phases under high temperature and high pressure conditions to form a large amount of nitrogen-rich phases. Among them, the nitrogen-rich phase formed by nitrogen elements in the grain boundaries can significantly improve the strength of the material through precipitation hardening. However, since NdFeB permanent magnets are prone to fracture along the grain boundaries, too much nitrogen-rich phase in the grain boundaries may cause the binding force between the grain boundary phase and the main phase to decrease, causing the magnet strength to decrease. The present invention further optimizes the nitrogen content distribution state in the airflow milling stage by controlling the grinding temperature at -5 to 10°C or the initial temperature of the grinding powder at 0 to 15°C, so that the proportion of nitrogen-rich phase to the grain boundary phase area is 10%<X1≤25%, thereby improving the magnetic properties of the magnet while improving the mechanical properties of the magnet.

[0053] According to an embodiment of the present invention, an antioxidant may be added to the jet mill powder obtained after the powder making process. The antioxidant may be any antioxidant known in the art, which is not specifically limited in the present invention. Exemplarily, the antioxidant is selected from fatty acid esters. Further, the antioxidant is added in an amount of 0.1 to 1 wt % of the jet mill powder, for example, 0.1 to 0.5 wt %.

[0054] According to the embodiment of the present invention, after the powder making process is completed, the particle size D50 of the jet mill is x (μm), the nitrogen content of the jet mill is u (wt%), and the nitrogen content of the alloy flakes is v (wt%), which must satisfy the following formulas (1) to (4):

[0055] 0.3≥(u-7v)*x≥0.04 (1)

[0056] 0.025≥v≥0.001 (2)

[0057] 0.08 ≥ u ≥ 0.02 (3)

[0058] 5.5≥x≥2.3 (4).

[0059] In the present invention, if the range of the above formula (1) is not satisfied, the nitrogen-rich phase and the nitrogen-poor phase cannot be formed, and / or the ratio of the nitrogen-rich phase to the nitrogen-poor phase is not within the specified range, which ultimately affects the magnetic properties and mechanical properties of the product.

[0060] Preferably, 0.2≥(u-7v)*x≥0.04.

[0061] According to an embodiment of the present invention, the press molding process can dry-mold the mixture (or airflow milled powder): for example, the mixture is filled into a mold configured in a magnetic field and pressurized to mold the mixture to obtain a molded body. At this time, by molding while applying a magnetic field, the mixture can be molded in a state where the crystal axis is oriented in a specific direction. In the press molding step, molding aids known in the art can be added as needed. Preferably, the pressure during pressurization can be, for example, greater than 8MPa and less than 300MPa; the applied magnetic field can be a static magnetic field and / or a pulsed magnetic field, and the magnetic field strength can be, for example, 2 to 5T. Alternatively, wet molding can also be used: for example, a slurry in which the mixture is dispersed in a solvent such as oil is molded to obtain a molded body.

[0062] Those skilled in the art will appreciate that there is no particular limitation on the specific shape of the molded body, which can be adjusted according to the application conditions of the permanent magnet. For example, the molded body can be a rectangular parallelepiped, a flat plate, a column, a ring, or a C-shaped shape.

[0063] According to an embodiment of the present invention, in the heat treatment step, the obtained compact is sintered in a vacuum or inert gas atmosphere.

[0064] According to an embodiment of the present invention, the temperature of the heat treatment is 950-1150°C, preferably 1000-1100°C.

[0065] According to an embodiment of the present invention, after the heat treatment process, a diffusion process may be optionally performed.

[0066] According to an embodiment of the present invention, in the diffusion process, a diffusion source is used to diffuse the product after the heat treatment process. Preferably, the diffusion source includes a heavy rare earth element RH, and the heavy rare earth element is selected from at least one of gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, lutetium and yttrium, preferably terbium.

[0067] Preferably, in the diffusion source, the mass content of heavy rare earth elements is not less than 60%, preferably not less than 70%.

[0068] According to an embodiment of the present invention, in the diffusion process, a diffusion source is coated on the surface of the product after the heat treatment process to perform diffusion treatment.

[0069] Preferably, the diffusion process includes a first diffusion process and a second diffusion process.

[0070] Specifically, the first diffusion treatment can be performed at a holding temperature of 800° C. to 1000° C. for 2 hours to 40 hours; the heating rate to the holding temperature can be 5° C. / min to 50° C. / min.

[0071] Specifically, the second diffusion treatment can be performed at a holding temperature of 450° C. to 650° C. for 2 hours to 20 hours. The speed of heating to the holding temperature can be 5° C. / min to 50° C. / min.

[0072] The present invention also provides the application of the sintered NdFeB permanent magnet in motors, loudspeakers, magnetic separators, computer disk drives, magnetic resonance imaging equipment, etc.

[0073] Exemplarily, the sintered NdFeB permanent magnet can be used as a motor rotor magnetic steel in a motor.

[0074] Beneficial Effects

[0075] In the production process of NdFeB permanent magnets, most of the process links are in argon or vacuum environment, not in nitrogen atmosphere. When a small amount of nitrogen atmosphere is exposed, the equipment is under normal temperature and pressure conditions, and there is no condition for introducing nitrogen. Based on this, the present invention controls the nitrogen content of each element in the raw materials during the smelting process to prepare alloy flakes with different nitrogen contents, and controls the nitrogen content of air flow milling, and combines the formula and particle size comprehensive regulation to achieve the control of the distribution position and enrichment state of nitrogen in the product.

[0076] Further research found that during the smelting stage, a melting temperature of 1300-1600°C and long-term electromagnetic stirring were used, and the nitrogen content introduced was relatively low. Therefore, the nitrogen in the scales existed simultaneously in the grain boundaries and the main phase grains, and some main phase grains had a higher nitrogen content than the adjacent grain boundaries, and nitrogen-poor phases appeared at the adjacent grain boundaries.

[0077] The permanent magnet formula of the present invention adopts a specific ratio of R, Cu and B, controls the nitrogen content of the product at different stages and the particle size of the airflow milling, regulates the relationship between the nitrogen content of the alloy flakes, the nitrogen content of the airflow milling and the particle size of the airflow milling (i.e., formula (1)), and especially intervenes in the formation stage of the nitrogen-rich phase and the nitrogen-poor phase, thereby ensuring the reasonable distribution of the nitrogen-rich phase and the nitrogen-poor phase, and achieving the simultaneous improvement of the mechanical properties and the magnetic properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0078] Figure 1 is a transmission electron microscope image of the nitrogen-rich phase of the permanent magnet of Example 1;

[0079] Figure 2 This is a transmission electron microscope image of the nitrogen-deficient phase of the permanent magnet of Example 1. DETAILED DESCRIPTION

[0080] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.

[0081] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.

[0082] Test method:

[0083] The magnetic properties, nitrogen content and bending strength of the sintered NdFeB permanent magnets prepared in the following Examples 1-4 and Comparative Examples 1-4 of the present invention were tested using the following testing equipment and methods:

[0084] Magnetic property test: NIM-62000 magnetic tester from China Institute of Metrology, 7-5-5mm standard test;

[0085] Nitrogen content: Remove the oxide layer on the magnet surface and then use the oxygen, nitrogen and hydrogen analyzer of Gangyan Nanok to analyze.

[0086] Bending strength: universal mechanical testing machine, 35-5-5mm standard test;

[0087] Area ratio calculation: Using a scanning transmission microscope JEOL-2010F, the grain boundary phase composition was analyzed at high magnification, and then in-situ observation was performed at low magnification. The ratio analysis of grain boundary phases with different contrasts was performed using Image-Pro Plus software.

[0088] Table 1 Permanent magnet raw materials and proportions of Examples 1-4 and Comparative Examples 1-4 (wt%)

[0089] PcqI Co Fe Al Ga Cu Zr B [R]-25*[Cu]-[B] Example 1 30 1 67 0.2 0.2 0.4 0.2 1 19 Example 2 30 1 67 0.2 0.2 0.4 0.2 1 19 Example 3 30 1 67 0.2 0.2 0.4 0.2 1 19 Example 4 31 1 65.3 0.2 0.2 1.1 0.2 1 2.5 Comparative Example 1 30 1 67 0.2 0.2 0.4 0.2 1 19 Comparative Example 2 30 1 67 0.2 0.2 0.4 0.2 1 19 Comparative Example 3 30 1 67 0.2 0.2 0.4 0.2 1 19 Comparative Example 4 29 1 67.1 0.2 0.2 1.3 0.2 1 -4.5

[0090] Example 1

[0091] The raw materials were configured according to the composition table of NdFeB materials in Table 1 (all in wt%), the N content in the selected PrNd, Fe and BFe raw materials is shown in Table 2, and the sintered NdFeB magnet was prepared by the following preparation method:

[0092] (1) The above raw materials were melted in an argon atmosphere at 1400°C according to the target ratio and maintained for 15 minutes. After the raw materials were homogenized, they were poured onto the surface of a rotating quenching roller. After cooling, NdFeB alloy flakes with a thickness of about 0.3 mm were obtained, and the nitrogen content of the flakes was tested.

[0093] (2) The alloy flakes obtained above are subjected to hydrogen absorption treatment, and the hydrogen absorption pressure is 0.2MPa. After hydrogen absorption, the magnet powder is placed in a material tank, and then the material tank is placed in a 5°C room for 6 hours, followed by air flow milling to obtain air flow milled powder with D50=3.1μm, and a small amount of air flow milled powder is taken to test the nitrogen content u(%). Antioxidant fatty acid ester is added to the air flow milled powder and mixed evenly to obtain alloy fine powder, and the content of antioxidant fatty acid ester accounts for 0.05wt% of the total weight of the air flow milled powder.

[0094] (3) Orient the alloy fine powder in a magnetic field, control the orientation field strength to be 2T, and then isostatically press at 170MPa to obtain a green compact. Place the green compact in a vacuum heat treatment sintering process, and control the sintering temperature to be 1065°C.

[0095] (4) The sintered green compact is machined into a substrate with a size of 35 mm*5 mm*5 mm, wherein the dimension in the orientation direction is 5 mm. Tb is arranged on the surface of the substrate by magnetron sputtering, and a diffusion heat treatment is performed. The diffusion heat treatment process includes: a primary heat treatment at a diffusion temperature of 940°C and a heat treatment time of 30 h; followed by a secondary heat treatment at 500°C and a heat treatment time of 10 h to obtain a permanent magnet.

[0096] Figure 1 This is a transmission electron microscope image of the nitrogen-rich phase of the permanent magnet of Example 1. The composition of the nitrogen-rich phase is R 69.8 Fe 5.8 Co0.2 Cu 6.2 B 2.9 N 15.1 .

[0097] Figure 2 This is a transmission electron microscope image of the nitrogen-poor phase of the permanent magnet of Example 1. The composition of the nitrogen-poor phase is R 54.3 Fe 30.9 Co 4.4 Cu 6.8 N 1.6 .

[0098] Table 2 Nitrogen content (a, b and c) in raw materials used for permanent magnet smelting of Examples 1-4 and Comparative Examples 1-4, nitrogen content v of flakes, particle size x of jet milling, nitrogen content u of jet milling and formula (1)

[0099]

[0100]

[0101] Example 2

[0102] The raw materials were configured according to the composition table of NdFeB materials in Table 1 (all in wt%), the N content in the selected PrNd, Fe and BFe raw materials is shown in Table 2, and the sintered NdFeB magnet was prepared by the following preparation method:

[0103] (1) Same as step (1) of Example 1.

[0104] (2) The alloy flakes obtained above are subjected to hydrogen absorption treatment, and the hydrogen absorption pressure is 0.2MPa. After hydrogen absorption, the magnet powder is placed in a material tank, and then subjected to airflow milling. The airflow mill refrigerator is turned on to reduce the grinding medium temperature to 4°C, and airflow milling powder with D50=3.1μm is obtained. A small amount of airflow milling powder is taken to test the nitrogen content u(%). Antioxidant fatty acid ester is added to the airflow milling powder and mixed uniformly to obtain alloy fine powder, and the content of antioxidant fatty acid ester accounts for 0.05wt% of the total weight of the airflow milling powder.

[0105] (3) Same as step (3) of Example 1.

[0106] (4) Same as step (4) in Example 1.

[0107] Example 3

[0108] The raw materials were configured according to the composition table of NdFeB materials in Table 1 (all in wt%), the N content in the selected PrNd, Fe and BFe raw materials is shown in Table 2, and the sintered NdFeB magnet was prepared by the following preparation method:

[0109] (1) Same as step (1) of Example 1.

[0110] (2) The alloy flakes obtained above are subjected to hydrogen absorption treatment, and the hydrogen absorption pressure is 0.2MPa. After hydrogen absorption, the magnet powder is placed in a material tank, and then the material tank is placed in a 5°C room as a whole for 6 hours, followed by air flow milling, turning on the air flow mill refrigerator, lowering the grinding temperature, and the grinding temperature is 4°C to obtain air flow milling powder with D50=3.5μm. A small amount of air flow milling powder is taken to test the nitrogen content u(%). Antioxidant fatty acid ester is added to the air flow milling powder and mixed evenly to obtain alloy fine powder, and the content of antioxidant fatty acid ester accounts for 0.05wt% of the total weight of the air flow milling powder.

[0111] (3) Same as step (3) of Example 1.

[0112] (4) Same as step (4) in Example 1.

[0113] Example 4

[0114] The raw materials were configured according to the composition table of NdFeB materials in Table 1 (all in wt%), the N content in the selected PrNd, Fe and BFe raw materials is shown in Table 2, and the sintered NdFeB magnet was prepared by the following preparation method:

[0115] (1) Same as step (1) of Example 1.

[0116] (2) The alloy flakes obtained above are subjected to hydrogen absorption treatment, and the hydrogen absorption pressure is 0.2MPa. After hydrogen absorption, the magnet powder is placed in a material tank, and then the material tank is placed in a 5°C room as a whole for 6 hours, followed by air flow milling, turning on the air flow mill refrigerator, lowering the grinding temperature, and the grinding temperature is 2°C to obtain air flow milling powder with D50=3.5μm. A small amount of air flow milling powder is taken to test the nitrogen content u(%). Antioxidant fatty acid ester is added to the air flow milling powder and mixed evenly to obtain alloy fine powder, and the content of antioxidant fatty acid ester accounts for 0.05wt% of the total weight of the air flow milling powder.

[0117] The alloy fine powder is oriented and pressed in a magnetic field, the orientation field strength is controlled to be 2T, and then is isostatically pressed at 170MPa to obtain a compact. The compact is placed in a vacuum heat treatment and sintered, and the sintering temperature is controlled to be 1065°C.

[0118] (3) Same as step (3) of Example 1.

[0119] (4) Same as step (4) in Example 1.

[0120] Comparative Example 1

[0121] The manufacturing method of Comparative Example 1 is basically the same as that of Example 1, except that:

[0122] In step (1), the N content in the raw materials is different;

[0123] In step (2), the alloy flakes obtained above are subjected to hydrogen absorption treatment at a hydrogen absorption pressure of 0.2 MPa. After hydrogen absorption, the magnet powder is placed in a material tank, and then subjected to jet milling at a grinding temperature of 30° C. to obtain jet milling powder with D50=3.1 μm. A small amount of jet milling powder is taken to test the nitrogen content u (%). Antioxidant fatty acid ester is added to the jet milling powder and mixed uniformly to obtain alloy fine powder, and the content of antioxidant fatty acid ester accounts for 0.05wt% of the total weight of the jet milling powder.

[0124] Comparative Example 2

[0125] The manufacturing method of this comparative example is basically the same as that of Example 2, except that:

[0126] In step (1), the N content in the raw materials is different, see Table 2 for details.

[0127] Comparative Example 3

[0128] The manufacturing method of this comparative example is basically the same as that of Example 1, except that:

[0129] In step (2), the alloy flakes obtained above are subjected to hydrogen absorption treatment, and the hydrogen absorption pressure is 0.2 MPa. After hydrogen absorption, the magnet powder is placed in a material tank for jet milling to obtain jet mill powder with D50=4.5 μm, and a small amount of jet mill powder is taken to test the nitrogen content u (%). The jet mill powder is added with an antioxidant fatty acid ester accounting for 0.05wt% of the total weight and mixed evenly to obtain alloy fine powder.

[0130] Comparative Example 4

[0131] The manufacturing method of this comparative example is basically the same as that of Example 3, except that:

[0132] In step (1), the N content in the raw materials is different, see Table 2 for details; the raw material ratios are different, see Table 1 for details.

[0133] In step (2), the alloy flakes obtained above are subjected to hydrogen absorption treatment, and the hydrogen absorption pressure is 0.2MPa. The magnet powder after hydrogen absorption is placed in a material tank, and then the material tank as a whole is placed in a 5°C room for 6 hours, and then subjected to air flow milling to obtain air flow milling powder with D50=3.1μm, and a small amount of air flow milling powder is taken to test the nitrogen content u(%). Antioxidant fatty acid ester is added to the air flow milling powder and mixed uniformly to obtain alloy fine powder, and the content of antioxidant fatty acid ester accounts for 0.05wt% of the total weight of the air flow milling powder.

[0134] Table 3 Permanent magnet products and performance tests of Examples 1-4 and Comparative Examples 1-4

[0135]

[0136]

[0137] By comparing Comparative Example 1, Comparative Example 3 and Example 1, due to the difference in N content in the raw materials and the airflow mill control parameters, the nitrogen content of the alloy flakes and airflow milled powder in Comparative Example 1 and Comparative Example 3 is relatively high, and does not satisfy Formula (1) (i.e., 0.3≥(u-7v)*x≥0.04), resulting in a high proportion of nitrogen-rich phase and a low proportion of nitrogen-poor phase. As a result, the Hcj and flexural strength of Comparative Example 1 and Comparative Example 3 are relatively low.

[0138] In Comparative Example 2, due to insufficient control over the nitrogen content of the raw materials, formula (1) is not satisfied (i.e., 0.3≥(u-7v)*x≥0.04). Although the nitrogen-rich phase ratio of the product of Comparative Example 2 finally meets 10-35wt%, the nitrogen-poor phase ratio is too high (the nitrogen-poor phase accounts for 87%), resulting in higher bending strength but lower magnetic properties Hcj.

[0139] In Comparative Example 4, although the nitrogen content in the raw materials and the air flow mill are reasonably controlled, due to the large deviation in composition, [R]-25*[Cu]-[B]≥0 cannot be satisfied. The nitrogen-rich phase ratio of the final product of Comparative Example 4 is too low, and the nitrogen-poor phase ratio is too high, resulting in low Hcj level and flexural strength of its magnetic properties.

[0140] The above is an exemplary description of the embodiments of the present invention. However, the protection scope of the present invention is not limited to the above embodiments. Any modification, equivalent substitution, improvement, etc. made by those skilled in the art within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A sintered NdFeB permanent magnet, characterized in that: The permanent magnet has main phase grains and grain boundary phases, wherein the grain boundary phases are located between the main phase grains; the components of the main phase grains include R2T 14 B; the grain boundary phase comprises a nitrogen-rich phase and a nitrogen-poor phase; wherein, The nitrogen-rich phase comprises R, T, N, M and B, wherein, by mass ratio, R accounts for 45-75wt%, T accounts for 1-20wt%, N accounts for 10-35wt%, M accounts for 5-10wt%, and B accounts for 1-4wt%; The nitrogen-poor phase comprises R, T, N and M, wherein, by mass ratio, R accounts for 45-75wt%, T accounts for 5-40wt%, N accounts for 0.01-5wt%, and M accounts for 10-35wt%; R is a rare earth element; M is at least one of Al, Cu, Ga, Zr, Ti, Nb and Mn; N is nitrogen; T is at least one of Fe and Co; and B is boron.

2. The permanent magnet according to claim 1, characterized in that The proportion of the nitrogen-rich phase to the area of ​​the grain boundary phase is X1, and the proportion of the nitrogen-poor phase to the area of ​​the grain boundary phase is X2, 10%<X1≤25%, 69%≤X2≤85%.

3. The permanent magnet according to claim 1, characterized in that The sintered NdFeB permanent magnet comprises the following components based on a mass ratio of 100%: R: 26-32 wt%, R is a rare earth element, which includes at least Nd and at least one selected from the following rare earth elements: Y, La, Ce, Pr, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Sc; M: 0.5-3wt%, M is at least one of Al, Cu, Ga, Zr, Ti, Nb, and Mn; N: 0.02-0.1 wt%, N is nitrogen; B: 0.9-1.1 wt%, B is boron; The balance is T and impurities, and T is at least one of Fe and Co.

4. The permanent magnet according to claim 3, characterized in that M includes at least Cu, and may also be selected from at least one of Al, Ga, Zr, Ti, Nb, and Mn; In addition, the content of Cu in the permanent magnet is 0.35-1.2 wt%. Preferably, [R]-25*[Cu]-[B]≥0, wherein [R], [Cu] and [B] are the mass percentages of R, Cu and B respectively.

5. The method for preparing a permanent magnet according to any one of claims 1 to 4, characterized in that: The method comprises: The raw materials for preparing the sintered NdFeB permanent magnet are sequentially subjected to a smelting process, a powder making process, a pressing process and a heat treatment process to prepare the sintered NdFeB permanent magnet.

6. The method according to claim 5, characterized in that In the smelting process, the nitrogen content of the rare earth raw material R used is a, the nitrogen content of T is b, and the nitrogen content of BT is c; a, b, c satisfy: a<50ppm, b<100ppm, c<50ppm.

7. The method according to claim 5, characterized in that The powder making process includes hydrogen embrittlement, medium grinding and / or air flow grinding. Preferably, during the jet milling process, the grinding temperature is between -5 and 10°C or the initial temperature of the ground powder is between 0 and 15°C.

8. The method according to claim 5, characterized in that After the powder making process is completed, the particle size D50 of the jet mill is x (μm), the nitrogen content of the jet mill is u (wt%), and the nitrogen content of the alloy flakes is v (wt%), which must satisfy the following formulas (1) to (4): 0.3≥(u-7v)*x≥0.04 (1) 0.025≥v≥0.001 (2) 0.08≥u≥0.02 (3) 5.5≥x≥2.3(4)。 9. The method according to claim 5, characterized in that The temperature of the heat treatment is 950-1150°C.

10. Use of the permanent magnet according to any one of claims 1 to 4 in a motor, a loudspeaker, a magnetic separator, a computer disk drive or a magnetic resonance imaging device. Preferably, it is used in electric motors as motor rotor magnets.

Citation Information

Patent Citations

  • R-T-B series permanent magnet and preparation method and application thereof

    CN118299137A

  • Method for preparing highly tough magnets by adding boron nitride nanotubes crystal-boundary phase

    CN101552065A

  • Nitride-phase-containing high-performance neodymium-iron-boron permanent magnet and manufacture method

    CN107275024A

  • R-T-B neodymium-iron-boron magnet and preparation method and application thereof

    CN114284017A

  • Sintered neodymium-iron-boron magnet with high corrosion resistance and high magnetic performance and preparation method of sintered neodymium-iron-boron magnet

    CN115360008A

Cited By

  • Sintered neodymium-iron-boron permanent magnet, preparation method therefor and use thereof

    WO2026144625A1